2018
DOI: 10.3390/jimaging4110132
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Surface Elevation Information in UAV Multispectral Images for Mapping Weed Patches

Abstract: Accurate mapping of weed distribution within a field is a first step towards effective weed management. The aim of this work was to improve the mapping of milk thistle (Silybum marianum) weed patches through unmanned aerial vehicle (UAV) images using auxiliary layers of information, such as spatial texture and estimated vegetation height from the UAV digital surface model. UAV multispectral images acquired in the visible and near-infrared parts of the spectrum were used as the main source of data, together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…In the original methods, the input features include topographic openness, which represents the dominance (positive) or enclosure (negative) of a landscape (Yokoyama et al, 2002). We used spatial texture (Zisi et al, 2018), CHM, and VIs instead of openness, and different combinations were tested.…”
Section: Overview Of the Methodsologymentioning
confidence: 99%
See 2 more Smart Citations
“…In the original methods, the input features include topographic openness, which represents the dominance (positive) or enclosure (negative) of a landscape (Yokoyama et al, 2002). We used spatial texture (Zisi et al, 2018), CHM, and VIs instead of openness, and different combinations were tested.…”
Section: Overview Of the Methodsologymentioning
confidence: 99%
“…The layers of spatial texture (Texture) information were created by applying a local variance filter (7 × 7 pixels) to the RGB image (Zisi et al, 2018). Spatial texture describes visual effects caused by spatial variation in tonal quantity over relatively small areas (Anys & He, 1995).…”
Section: Spatial Texturementioning
confidence: 99%
See 1 more Smart Citation
“…Classification accuracy could be enhanced by combining RF classifier with OBIA (de Castro et al., 2018). In addition, previous studies have reported that weed detection from UAV images could be improved using auxiliary information layers, such as spatial texture and vegetation height estimated from UAV digital surface models (DSM) (Zisi et al., 2018). From these earlier findings, we can expect improvement of weed detection accuracy by combining OBIA and RF classification using UAV’s color images and its auxiliary information.…”
Section: Introductionmentioning
confidence: 99%
“…They are used as toys, platforms for commerce, or as vehicles for the testing and validation of advanced research topics in various scientific fields. There have been numerous instances of drones used in civilian applications such as aerial photography for various applications [1,2], crop monitoring [3,4], infrastructure assessment [5], as well as in disaster recovery [6], law enforcement, and many other applications.…”
Section: Introductionmentioning
confidence: 99%